Community awareness, use and preference for pandemic influenza vaccines in Pune, India - Sundaram, Neisha (Hum Vaccin Immunother, 2015)
Vaccination is a cornerstone of influenza prevention, but limited vaccine uptake was a problem worldwide during the 2009–2010 pandemic. Community acceptance of a vaccine is a critical determinant of its effectiveness, but studies have been confined to high-income countries. We conducted a cross-sectional, mixed-method study in urban and rural Pune, India in 2012–2013. Semi-structured explanatory model interviews were administered to community residents (n = 436) to study awareness, experience and preference between available vaccines for pandemic influenza. Focus group discussions and in-depth interviews complemented the survey. Awareness of pandemic influenza vaccines was low (25%). Some respondents did not consider vaccines relevant for adults, but nearly all (94.7%), when asked, believed that a vaccine would prevent swine flu. Reported vaccine uptake however was 8.3%. Main themes identified as reasons for uptake were having heard of a death from swine flu, health care provider recommendation or affiliation with the health system, influence of peers and information from media. Reasons for non-use were low perceived personal risk, problems with access and cost, inadequate information and a perceived lack of a government mandate endorsing influenza vaccines. A majority indicated a preference for injectable over nasal vaccines, especially in remote rural areas. Hesitancy from a lack of confidence in pandemic influenza vaccines appears to have been less of an issue than access, complacency and other sociocultural considerations. Recent influenza outbreaks in 2015 highlight a need to reconsider policy for routine influenza vaccination while paying attention to sociocultural factors and community preferences for effective vaccine action.